Generating Political Priority for Primary Health Care Reform in Romania - Wang, Huihui (Taylor and Francis, 2021)
This paper examines how political priority was generated for comprehensive reforms to address inequitable access to high-quality primary health care (PHC) in Romania. We apply John Kingdon’s model of political agenda setting to explore how the convergence of problems, solutions, and political developments culminated in the adoption of a government program that included critical PHC reforms and approval of a results-based funding instrument for implementation. We draw on a review of the gray and peer-reviewed literature and stakeholder consultations, and use content analysis to identify themes organized in line with the dimensions of Kingdon’s model. We conclude this paper with three lessons that may be relevant for generating political priority for PHC reforms in other contexts. First, national PHC reforms are likely to be prioritized when there is political alignment of health reforms with the broader political agenda. Second, the availability of technically sound and feasible policy proposals makes it possible to seize the political opportunity when the window opens. Third, partners’ coordinated technical and financial support for neglected issues can serve to raise their priority on the political agenda.